Membangun Hubungan Interpersonal Positif Melalui Kesepadanan Kalimat Tanya dan Unsur Nonverbal di Kelas I Sekolah Dasar - Taufina, Taufina (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Interrogative sentences are one form of verbal communication commonly used in classroom interaction. This type of sentence should be synchronized with its nonverbal elements. It is believed that verbal communication accompanied by appropriate nonverbal elements provides the basis for developing positive thinking patterns and students’ behavior, especially among first-grade primary school students. Therefore, teachers’ ability to synchronize interrogative sentences with their nonverbal elements is essential. Such a skill helps teachers enhance students’ self-confidence and enthusiasm for learning. Furthermore, it can establish positive interpersonal relationships between teachers and students. Hence, teachers, as one of the key factors determining the success of the learning process, should pay close attention to the synchronization of interrogative sentences and their nonverbal elements in order to create a conducive and interactive classroom atmosphere.